Teachers’ Perceptions of Students who Bully Teachers - Itani, Leah (2021)
Teaching is one of the most stressful professions. Teachers are frequently confronted with numerous disruptive bullying acts, resulting in lost classroom instruction time. Teachers’ wellbeing is an essential factor of student success, quality of instruction, and school culture. When referring to school bullying, it is generally assumed that students are the victims of such aggressions. However, little attention is given to student-to-teacher bullying and the way it affects teachers. This purpose of this pilot explanatory study is to explore teachers’ perceptions of teachers’ bullying by students, explore different types of bullying, and recommend proactive solutions. Peer-reviewed studies on the subject was examined in order to gain a better knowledge of bullying and to create a self-administered survey that addressed these concerns. This study is both qualitative and quantitative in nature and took place in a private school in Beirut. The research design consisted of focus groups with witnesses of bullying incidents, individual interviews with bullied teachers, and two questionnaires addressed to all teachers. A total of 53 teachers filled out the questionnaires, of which 10 accepted to be interviewed. The results of this study highlight the need of recognizing bullying in its various forms, correctly responding to bullying when it occurs, and including preventative measures that will discourage bullying and foster acceptance. Further research is needed on a larger sample of public and private Lebanese schools to explore this phenomenon on a national scale, also soliciting the input of students to gain a better understanding of the dynamics involved in bullying teachers.